2019
DOI: 10.5005/jp-journals-10024-2646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Papain and Bromelain Enzymes on Shear Bond Strength of Composite to Superficial Dentin in Different Adhesive Systems

Abstract: Aim:The aim of this study was to compare different dentin treatments and adhesive systems on shear bond strength (SBS) of composite to superficial dentin. Materials and methods: In this in vitro experimental study, 60 extracted human upper premolars were cut 0.5 mm deep under occlusal DEJ and were randomly divided into six groups (n = 10) based on the method of dentin treatment and adhesive system: (A) two steps self-etch adhesive system (Clearfil SE bond) and (B) two steps of total etch bonding system (Adper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…Moreover, Chauhan et al [9] reported that dentin deproteinization and removal of unsupported collagen fiber with bromelain enzyme after acid etching was able to statistically improve the SBS of the adhesive system. Sharafeddin et al evaluated the effect of 10% papain and 6% bromelain enzymes on bond strength to superficial dentin using different adhesive systems [3]. ey concluded that bond strength could be affected by the dissolution of collagen fibrils and change of the fibril composition may also be an effective factor in monomer diffusion by increasing dentin permeability [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Chauhan et al [9] reported that dentin deproteinization and removal of unsupported collagen fiber with bromelain enzyme after acid etching was able to statistically improve the SBS of the adhesive system. Sharafeddin et al evaluated the effect of 10% papain and 6% bromelain enzymes on bond strength to superficial dentin using different adhesive systems [3]. ey concluded that bond strength could be affected by the dissolution of collagen fibrils and change of the fibril composition may also be an effective factor in monomer diffusion by increasing dentin permeability [3].…”
Section: Discussionmentioning
confidence: 99%
“…Sharafeddin et al evaluated the effect of 10% papain and 6% bromelain enzymes on bond strength to superficial dentin using different adhesive systems [3]. ey concluded that bond strength could be affected by the dissolution of collagen fibrils and change of the fibril composition may also be an effective factor in monomer diffusion by increasing dentin permeability [3]. erefore, the type of the adhesive system and the deference in the composition of enamel and dentin could be an important factor on SBS when using bromelain and papain enzymes on tooth structure [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that some parameters such as cavity preparation and the percentage of bromelain enzymes that were used in their study were different from the current research, our results are favourable. Sharafeddin and Safari [19] A B C D in 2019 reported that using 6% bromelain enzyme before acid-etching had no impact on SBS of composite to superficial dentin; however, it could be related to the different steps of using the enzymes within our study. This finding does not endorse previous studies [2,6].…”
Section: Discussionmentioning
confidence: 54%
“…It was widely used in dentistry research because it has a high solubility in water, does not contain toxic substances, and has antibacterial activity [17,18]. Also it was used orally or topically for wounds and burns [19,20].…”
Section: O R I G I N a L Pa P E Rmentioning
confidence: 99%